2011
DOI: 10.1002/qua.22491
|View full text |Cite
|
Sign up to set email alerts
|

First principles investigation on the key factors of broad absorption spectra and electronic properties for oligothiophene and its derivatives for solar cells

Abstract: On the basis of optimized structures of two kinds thiophene oligomers, we investigated the configuration and conformation dependent optical and electronic properties of a or b substituted oligothiophene (PT) and oligo(thienylenevinylene) (PTV) isomers, respectively, at the TD-DFT/6-31þG(d,p)//PBE0/6-31G(d) level. The corresponding properties of polymers were predicted by extrapolation method. The broad absorption regions for polythiophene and/or poly(thienylenevinylene) can be ascribed to the coexistence of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…Recent DFT studies at the www.chemeurj.org comparable PBE0/6-31G(d) level of theory have shown that the torsion of the outermost ring of tetrakis(2-thienyl) with respect to the second ring exhibits two minima, at about 20 and about 1508 with barriers of rotation of 3.1 and 2.5 kcal mol À1 , respectively. [23] This correlates well with the experimentally observed non-coplanarity of bithiophene in gas phase.…”
Section: Introductionsupporting
confidence: 79%
“…Recent DFT studies at the www.chemeurj.org comparable PBE0/6-31G(d) level of theory have shown that the torsion of the outermost ring of tetrakis(2-thienyl) with respect to the second ring exhibits two minima, at about 20 and about 1508 with barriers of rotation of 3.1 and 2.5 kcal mol À1 , respectively. [23] This correlates well with the experimentally observed non-coplanarity of bithiophene in gas phase.…”
Section: Introductionsupporting
confidence: 79%
“…The 6-31G(d) split valence polarized basis set was used throughout because it has been tested extensively and has been shown to yield reliable results for geometries and electronic properties of organic semiconducting materials. [20][21][22][23][24][25] The PBE1PBE 26,27 (also called PBE0) has been recognized to provide reliable predictions and interpretations of the molecular geometries, electronic properties, and optical properties of organic compounds bearing sulfur atoms. [28][29][30][31][32][33] To check the consistency of our calculation, preliminary density functional theory (DFT) and time-dependent density functional theory (TD-DFT) calculations were performed on BDT and the results were compared with available experimental data.…”
Section: Methodology 21 Computational Detailsmentioning
confidence: 99%
“…Besides the ease of synthesis and modification of their structures, these azomethine-linked oligomers have numerous advantages in optical and hole/electron transport properties. ,,, Looking at the advantages of these linkages, a number of experimental and computational studies have been carried out to explore the structural details and usability of these heterocyclic conjugated polymers. These polymers have many different possible conformations. , Stabilities of these conformations are discussed in the literature, , but all the results are from studies on small (2 to 4 repeating units) linear oligomers. However, it is known that the intramolecular noncovalent interaction has a major impact on secondary structures like helices for a large π-conjugated oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers have many different possible conformations. 28,41 Stabilities of these conformations are discussed in the literature, 28,41 but all the results are from studies on small (2 to 4 repeating units) linear oligomers. However, it is known that the intramolecular noncovalent interaction has a major impact on secondary structures like helices for a large π-conjugated oligomer.…”
Section: Introductionmentioning
confidence: 99%